El estado actual de la aplicación del sistema de costos por proyecto de la empresa constructora ABC - Huamanyauri Cuellar, Vianney Margarita (2024)
The main objective of this research work was to propose improvements to the cost system of the construction company ABC. This highlights the importance of cost management for the construction sector, which is characterized by executing projects with high risk. This study used a qualitative case study approach, was descriptive in scope, and had a non-experimental and cross-sectional design. In the first stage of the fieldwork, data was collected from the selected company. In the second stage, the data was analyzed and interpreted applying the concepts, costing techniques obtained in the review of the scientific literature on cost management and documentary analysis. Once these stages were developed, we proceeded to propose the pertinent improvements according to the company's needs. In light of the results obtained from this research, reliable and timely cost information is a competitive advantage for the company. To do this, it is necessary to design and implement an efficient and effective project costing system capable of providing quality, timely and reliable information, with which top management can make better decisions for the company's benefit. This study can also guide other companies in the same sector with similar characteristics and needs.